Sistem Informasi Penjualan Dan Pengelolaan Budidaya Tambak Lobster Berbasis Web Menggunakan Metode Agile (Studi Kasus : Blue Claw Fish Farm) - Suranta, Rahmatdin; Nirmala, Endar (CV. Shofanah Media Berkah, 2023)
Internet technology has a huge effect on commerce or business. Can access information on goods from anywhere, from prices, specifications, stock of goods, and can carry out transaction activities at any time. In research conducted at the Blue Claw Fish Farm shop, it was still found that there were problems with limited information on lobster cultivation that the store could provide to consumers, and the sales system was not optimal because it only made direct sales to consumers who came to the store, as well as managing goods and financial data. still using bookkeeping, allowing for data loss and calculation errors and delays when making reports. The method used in this study is the Agile method which is a method with agreed rules and solutions carried out in collaboration between teams in an organized and regular manner. The results of these studies make information can be widely spread and sales activities become easier and more efficient online and make it easier for staff to manage goods data, finance and report generation.